A queer history of the United States - Bronski, Michael (ReVisioning American history, 2011)
"A Queer History of the United States looks at how American culture has shaped the LGBT, or queer, experience. Also argues that LGBT people were pivotal in creating our country. Using numerous primary documents and literature, as well as social histories, Bronski's book takes the reader through the centuries --from Columbus' arrival and the brutal treatment the Native peoples received, through the American Revolution's radical challenging of sex and gender roles --to the violent, and liberating, 19th century, and the transformative social justice movements of the 20th. Bronski's book is filled with startling examples of often ignored or unknown aspects of American history: the ineffectiveness of sodomy laws in the colonies, the prevalence of cross-dressing women soldiers in the Civil War, the effect of new technologies on LGBT life in the 19th century, and how rock music and popular culture were, in large part, responsible for the great backlash against gay rights in the late 1970s. A Queer History of the United States is not so much about queer history as it is about all American history--and why it should matter to both LGBT people and heterosexuals alike"--